2012
DOI: 10.1371/journal.pone.0033770
|View full text |Cite
|
Sign up to set email alerts
|

Global Methylation Patterns in Idiopathic Pulmonary Fibrosis

Abstract: BackgroundIdiopathic Pulmonary Fibrosis (IPF) is characterized by profound changes in the lung phenotype including excessive extracellular matrix deposition, myofibroblast foci, alveolar epithelial cell hyperplasia and extensive remodeling. The role of epigenetic changes in determining the lung phenotype in IPF is unknown. In this study we determine whether IPF lungs exhibit an altered global methylation profile.Methodology/Principal FindingsImmunoprecipitated methylated DNA from 12 IPF lungs, 10 lung adenocar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
120
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(126 citation statements)
references
References 73 publications
(95 reference statements)
3
120
0
3
Order By: Relevance
“…Genome-wide methylation arrays show that 402 differentially methylated CpG islands overlapped between IPF and lung cancer, three genes expression positive correlation with hypomethylated promoters (32). The Human Methylation 27 array find that multiple CpG sites across the genome are differentially methylated in IPF fibroblasts (33).…”
Section: Measure the Pten And C-jun Methylation Status In Helfsmentioning
confidence: 99%
“…Genome-wide methylation arrays show that 402 differentially methylated CpG islands overlapped between IPF and lung cancer, three genes expression positive correlation with hypomethylated promoters (32). The Human Methylation 27 array find that multiple CpG sites across the genome are differentially methylated in IPF fibroblasts (33).…”
Section: Measure the Pten And C-jun Methylation Status In Helfsmentioning
confidence: 99%
“…Myofibroblasts are the primary contributors to fibrosis, which drives some invasive cancers, especially liver cancer (Pinzani et al, 2005;de Wever et al, 2008). Many studies have explored methylation changes in fibrotic diseases such as hepatic, pulmonary, and renal fibrosis (Mann et al, 2010;Rabinovich et al, 2012;Tampe et al, 2014). Gotze et al (2015) found global DNA hypomethylation in the early stage of hepatic stellate cell (HSC) activation, similar to the findings in CAFs.…”
Section: Dna Methylation In Cancer-associated Fibroblastsmentioning
confidence: 73%
“…The IPF samples were then compared to samples from lung cancer patients; the lung cancer samples were found to have 2428 differentially methylated CpG islands when compared to healthy tissue samples. 65% of the differentially methylated CpG islands methylated in IPF samples were also seen in the lung cancer samples (Rabinovich et al, 2012).…”
Section: Methylationmentioning
confidence: 92%
“…how frequently methylated-CpG sequences occur within the gene, and also on the location of the methylation in relation to the promoter region of the gene (Bian et al, 2013;Hsieh, 1994) Epigenetic changes have been linked to many diseases including cardiovascular disease (Webster et al, 2013); as well as colon, lung, breast and thyroid cancer, where large hypomethylated blocks of the genomes have been found (Hansen et al, 2011) and promoter hypermethylation of classic tumour suppressor genes are found. More recently, methylation changes have been associated with fibrotic diseases such as hepatic, pulmonary, renal and cardiac fibrosis (Mann et al, 2010;Rabinovich et al, 2012;Tampe et al, 2014;Xu et al, 2015). Numerous genes have been found to be involved in this association and those referred to in this review are listed in Table 2.…”
Section: Methylationmentioning
confidence: 99%